Outcomes of surgically treated human papillomavirus–related oropharyngeal squamous cell carcinoma with N3 disease. (23rd December 2016) - Zenga, Joseph; Haughey, Bruce H.; Jackson, Ryan S.; Adkins, Douglas R.; Aranake‐Chrisinger, John; Bhatt, Neel; Gay, Hiram A.; Kallogjeri, Dorina; Martin, Eliot J.; Moore, Eric J.; Paniello, Randal C.; Rich, Jason T.; et al.
Abstract : Objectives/Hypothesis: To evaluate outcomes for patients with pathological N3 (pN3) neck disease from human papillomavirus (HPV)–related oropharyngeal squamous cell carcinoma (OPSCC) and determine variables predictive of survival. Study Design: Retrospective case series with chart review. Methods: This study was conducted between 1998 and 2013 and included patients with HPV‐related OPSCC treated with surgery with or without adjuvant therapy and who had pN3 nodal disease. The primary outcome was disease‐specific survival (DSS). Secondary outcomes included overall survival (OS), disease‐free survival (DFS), adverse events, and gastrostomy tube rates. Results: Thirty‐nine patients were included, of whom 36 (90%) underwent adjuvant therapy. Median follow‐up was 39 months (range, 2–147 months). Mean age was 56 years, and 87% were male. Seventeen patients (44%) underwent selective neck dissection, whereas six (15%) underwent radical (n = 2) or extended radical (n = 4) neck dissection. Ninety‐two percent had extracapsular extension. Five‐year Kaplan‐Meier estimated DSS, OS, and DFS were 89% (95% confidence interval [CI]: 79%–99%), 87% (95% CI: 75%–99%), and 84% (95% CI: 72%–96%), respectively. The disease recurrence rate was 10% (5% regional, 5% distant metastasis). Patients with less than 5 pathologically positive lymph nodes ( P = .041) had improved DFS. Conclusions: Patients with HPV‐related OPSCC and pN3 nodal disease treated with surgery and adjuvant therapy have very favorable long‐term survival and regional control. Patients with five or more pathologically positive lymph nodes may be at higher risk for recurrence. Level of Evidence: 4. Laryngoscope, 127:2033–2037, 2017